Pengaruh Model Pembelajaran Problem Based Learning terhadap Kemampuan Menulis Cerita Pendek - Kholillah, Rida; Firdaus, Asep; Humaira, Hera Wahdah (Universitas Muhammadiyah Kotabumi, 2025)
This study aims to determine the effect of the application of the Problem Based Learning learning model on the ability to write short stories for grade XI MAS Darul Mutaallimien students for the 2024/2025 school year. The type of research used is quantitative research with an experimental method, in the form of One-Group Pretest-Posttest Design. The research subjects consisted of 26 students of class XI B MAS Darul Mutaallimien for the 2024/2025 school year. The data collection techniques used include tests, observations and documentation. Based on the results of initial observations through the pretest, it was shown that the student's score of writing short stories was 59.69. This shows that students' ability to write short stories is relatively low. However, after students were given treatment in the form of applying the Problem Based Learning learning model and conducting a posttest, there was a significant increase in the average score of students to 79.81. Therefore, a t-test was carried out with a significance value of 0.000<0.05, in addition to a hypothesis test was carried out that showed that the tcount (9,720) was greater than the ttable (1,704). This shows that H0 is rejected and H1 is accepted. Thus, it can be stated that the Problem Based Learning learning model has an effect on the ability to write short stories for grade XI MAS Darul Mutaallimien students for the 2024/2025 school year.